Flame-Retardant Properties and Mechanism of Polylactic Acid-Conjugated Flame-Retardant Composites - Zhang, Daohai; Pei, Meng; Wei, Ke; Tan, Fang; Gao, Chengtao; Bao, Dongmei; Qin, Shuhao (Frontiers in Chemistry, 2022)
The DOPO derivative conjugated flame retardant 4, 4'-{1'', 4'' - phenylene - bis [amino - (10''' - oxy -10'''-hydro-9'''-hydrogen-10''' λ5 -phosphaphenanthrene-10''-yl)-methyl]}-diphenol (P-PPD-Ph) with two hydroxyl groups was synthesized. Polylactic acid conjugated flame retardant composites with P-PPD-Ph and epoxy chain extender were papered by using a twin screw extruder. The flame retardant properties of Polylactic acid conjugated flame retardant composites was investigated. The flame retardant properties of PLA conjugated flame retardant composites were characterized by the limiting oxygen index (LOI), the vertical burning test (UL94). The results showed that the PLA conjugated flame retardant composites achieved a V-0 rating (UL-94, 3.2 mm) when the flame retardant was added at 5 wt%, and the LOI values of PLA conjugated flame retardant composites increased from 22.5% to 31.4%. The flame retardant mechanism of PLA conjugated flame retardant composites were further studied by TG-FTIR, the results that the P-PPD-Ph promoted the PLA conjugated flame retardant composites decompose earlier, and also releasing fragments with quenching and dilution, which suggests that P-PPD-Ph for PLA conjugated flame retardant composites mainly play a role of gas phase flame retardant.